Physiotherapy Management in Cases of Stiffness Elbow Joint Sinistra ec Posterior Dislocation of Elbow Joint Sinistra at RSUD Salatiga - Izzuddin, Amar Maulana; Komalasari, Dwi Rosella; Yanuar, Reza Arshad (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Elbow dislocation is the second most frequently dislocated joint in adults after the shoulder. The incidence of elbow dislocations in the United States is. 7,000 per year. Elbow dislocation can cause stiffness in the elbow. This impacts pain, muscle spasms, limited range of motion and functional activities. Hence, therapy for elbow dislocation can be in the form of deep friction massage, muscle energy technique and exercise therapy. Case Presentation: This study reported a women patient, aged 21 years old with posterior elbow dislocation in sinistra side because fallen on July 2023. After a month, the patient was done for surgery at Orthopaedic Hospital of Surakarta and then referred to RSUD Salatiga to do intensive physiotherapy treatment. Management and Outcome: There were pain arround elbow by NRS, limited range of motion by goniometer, reduce muscle strength by MMT and reduced functional activities by DASH scale. Patient got deep friction massage, MET and exercise therapy 5 times Discussion: There were significant improvement form pain where tenderness (3 to 2) and movement pain (4 to 3), increasing extension range of motion from 350 to 250 especially for sagital plane, increasing muscle strength m. biceps brachii (4 to 5), as well improving score of DASH of functional activities from 5 to 25. Conclusion: Comprehensive treatment of Physiotherapy techniques gives positive effects to patient with the condition of elbow dislocation. This study might can be a reference to guide other physiotherapist doing rehabilitation to the patient with elbow dislocation.